(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This scientific article provides an in-depth examination of American-based pronunciation standards of English. With English being a global language, various pronunciation standards have emerged due to regional differences. This article focuses on the American accent and explores the key features, characteristics, and influences of American English pronunciation. It also discusses the impact of American-based pronunciation standards on English language teaching and the diverse challenges that learners may encounter when striving to achieve proficiency in American English pronunciation.